Never sleep again : the Elm Street legacy [videorecording (DVD)] - Kasch, Andrew, 1979-; Kasch, Andrew, 1979-; Hutson, Thommy; Langenkamp, Heather, 1964-
A thrilling "shockumentary" that takes you deeper into Freddy's realm than ever before, featuring exciting clips, never-before-seen photos, behind-the-scenes footage, conceptual art, publicity materials and exclusive new interviews with over 100 key cast and crew from every Nightmare.